Modulation of Allergic Sensitization and Allergic Inflammation by Staphylococcus aureus Enterotoxin B in an Ovalbumin Mouse Model - Jorde, Ilka; Hildebrand, Christina B.; Kershaw, Olivia; Lücke, Eva; Stegemann-Koniszewski, Sabine; Schreiber, Jens (Frontiers in Immunology, 2020)
The superantigen Staphylococcus aureus (S. aureus) enterotoxin B (SEB) has been proposed a central player in the associations between S. aureus nasal colonization and the development of allergic asthma. Previously, SEB has been shown to aggravate allergic sensitization and allergic airway inflammation (AAI) in experimental mouse models. Aiming at understanding the underlying immunological mechanisms, we tested the hypothesis that intranasal (i.n.) SEB-treatment divergently modulates AAI depending on the timing and intensity of the SEB-encounter. In an ovalbumin-mediated mouse model of AAI, we treated mice i.n. with 50 ng or 500 ng SEB either together with the allergic challenge or prior to the peripheral sensitization. We observed SEB to affect different hallmark parameters of AAI depending on the timing and the dose of treatment. SEB administered i.n. together with the allergic challenge significantly modulated respiratory leukocyte accumulation, intensified lymphocyte activation and, at the higher dose, induced a strong type-1 and pro-inflammatory cytokine response and alleviated airway hyperreactivity in AAI. SEB administered i.n. prior to the allergic sensitization at the lower dose significantly boosted the specific IgE response while administration of the higher dose led to a significantly reduced recruitment of immune cells, including eosinophils, to the respiratory tract and to a significantly dampened Th-2 cytokine response without inducing a Th-1 or pro-inflammatory response. We show a remarkably versatile potential for SEB to either aggravate or alleviate different parameters of allergic sensitization and AAI. Our study thereby not only highlights the complexity of the associations between S. aureus and allergic asthma but possibly even points at prophylactic and therapeutic pathways.